Identification of Neuropeptides and Their Receptors in the Ectoparasitoid, Habrobracon hebetor - Yu, Kaili; Xiong, Shijiao; Xu, Gang; Ye, Xinhai; Yao, Hongwei; Wang, Fang; Fang, Qi; Song, Qisheng; Ye, Gongyin (Frontiers in Physiology, 2020)
Neuropeptides are a group of signal molecules that regulate many physiological and behavioral processes by binding to corresponding receptors, most of which are G-protein-coupled receptors (GPCRs). Using bioinformatic methods, we screened genomic and transcriptomic data of the ectoparasitoid wasp, Habrobracon hebetor, and annotated 34 neuropeptide candidate precursor genes and 44 neuropeptide receptor candidate genes. The candidate neuropeptide genes were found to encode all known insect neuropeptides except allatotropin, neuropeptide F, pigment dispersing factor, and CCHamides. When compared with the endoparasitic wasp Pteromalus puparum and the ectoparasitic wasp Nasonia vitripennis, trissin and FMRFamide were found only in H. hebetor. A similar result held for the neuropeptide receptor genes, for the receptors were found in H. hebetor except the receptors of CCHamides and neuroparsin. Furthermore, we compared and analyzed the differences in neuropeptides in eight Braconidae wasps and identified natalisin in H. hebetor, Diachasma alloeum, Fopius arisanus and Microplitis demolitor, but not in the other wasps. We also analyzed the transcriptome data and qRT-PCR data from different developmental stages and tissues to reveal the expression patterns of the neuropeptides and their receptors. In this study, we revealed composition of neuropeptides and neuropeptide receptors in H. hebetor, which may contribute to future neurobiological studies.